Marketing Strategy of PT PACC to Increase Consumer Interest in Buying Gadget Accessories: Consumer Perspective - Alexandro Manuel (Indonesian Journal of Economics, Business, Accounting, and Management (IJEBAM), 2024)
PT PACC is a retail company engaged in the sale of gadget accessories in Yogyakarta and Central Java. The company faces the challenge of ineffective marketing and the presence of competitors, making it difficult to attract loyal customers. This study aims to analyze the factors that influence consumer purchasing interest and evaluate the marketing strategy of the PACC store. This internship program focuses on analyzing consumer perspectives using descriptive qualitative methods with interview techniques, observations and documentation studies. The results show that the implementation of 4P strategy (product, price, place, promotion) affects consumer purchasing interest. However, it was found that the marketing strategy used by the PACC store still needs to be improved to be more effective